In Situ Evaluation of Fludarabine-DNA Interaction Using a DNA-Electrochemical Biosensor - H. Eda Satana; Ana Maria Oliveira-Brett (International Journal of Electrochemistry)
Fludarabine, 9-β-D-arabinosyl-2-fluoroadenine, the nucleoside analog, represents a highly effective treatment for hairy cell leukemia. The electrochemical behaviour of fludarabine is an irreversible diffusion controlled oxidation mechanism and was investigated at a glassy carbon electrode in different supporting electrolytes using cyclic, differential pulse, and square wave voltammetry. The diffusion coefficient of fludarabine was calculated to be DFLU=1.71×10−6 cm2 s-1 in pH 7.0 0.1 M phosphate buffer. The oxidation mechanism of fludarabine occurs with the transfer of one proton and one electron and the formation of a hydroxylated species. The interaction of fludarabine with DNA was investigated, by differential pulse voltammetry, in incubated solutions and using dsDNA- and polyhomonucleotides-, poly[G] and poly[A], electrochemical biosensors. The results showed that fludarabine interacts with DNA causing changes in the DNA structure.